Water Discharge and River Depth Measurement Using Fuzzy Logic Based on Internet of Things - Kurnia Wisuda Aji; Aji Gautama Putrada; Sidik Prabowo; Mas'ud Adhi Saputra (Ikatan Ahli Informatika Indonesia (IAII), 2020)
Based on statistics from Indonesian National Board for Disaster Management (BNPB) there are still many casualties caused by drifting or drowning in rivers every year. This is because most victims do not have sufficient information related to water discharge and river depth. In an effort to reduce the potential victims of these problems, a prototype was designed to provide a warning regarding river status as a display in the detail condition of the river in real-time. In this research, a prototype measuring instrument was produced that could provide information on water discharge and river depth in a sustainable and real-time manner. The prototype device consists of two main sensors as an implementation of internet of things, a water flow sensor and an ultrasonic sensor. Water flow sensor used to calculate the water discharge, and ultrasonic sensor used to measure depth of the river. Fuzzy logic has been used because it can work well for simple classification and work similarly like human reasoning. This information can be monitored through the website and LCD attached on the device. The results of the study with the help of the Linear Congruential Generator (LCG) method indicated that greater input value of the water discharge and the river depth caused more dangerous of the river status. Whereas the prototype produced has an error range of 5-6 cm for depth information generated by the ultrasonic sensor while the accuracy of the water flow sensor on the master device is 79.75% and the slave device is 84%.